Hazard analysis on public-private partnership projects in developing Asia - Minsoo Lee; Xuehui Han; Pilipinas Quising; Mai Lin Villaruel (Asian Development Bank (ADB), 2018)
Developing Asia's infrastructure gap results from both inadequate public resources and a lack of effective channel to mobilize private resources toward desired outcomes. The public-private partnership (PPP) mechanism has evolved to fill the infrastructure gap. However, PPP projects are often at risk of becoming distressed or worst being terminated because of the long-term nature of contracts and the many different stakeholders involved. This paper applies survival time hazard analysis to estimate how project-related, macroeconomic, and institutional factors affect the hazard rate of the projects. Empirical results show that government's provision of guarantees, involvement of multilateral development banks, and existence of a dedicated PPP unit are important for a project's success. Privately initiated proposals should be regulated and undergo a competitive bidding to reduce the hazard rate of the project and the corresponding burden to government. Economic growth leads to successful project outcomes. Improved legal and institutional environment can ensure PPP success.
Keywords: F21; H54; H81; 330; infrastructures; investment policy; public-private partnership; survival analysis